2021
DOI: 10.2478/asmj-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of two-way relationship between periodontal diseases and diabetes mellitus.

Abstract: Periodontal disease and diabetes mellitus have been said to have a two-way relationship, with diabetes leading to oral disease and periodontitis exacerbating hyperglycemia. The universal biologic mechanisms and demographic and behavioral risk drivers, underlying these associations in both directions, are also described.Both the diseases are chronic and they are affecting large population worldwide. Periodontitis is also recognized as the sixth major complication of diabetes, while diabetes mellitus is a metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Prevention and treatment of pathologies in the superficial and deep marginal periodontium must be judiciously considered in the management of patients with hyperglycemia. It has been shown that keeping blood sugar levels under control has advantages over periodontal disease, while the treatment of periodontal disease improves metabolism in patients with diabetes [86]. Clear health strategies need to focus on periodontal disease, as a risk factor for diabetes and cardiovascular disease, through prevention and treatment programs for all chronic infections [87].…”
Section: T Forsythia a Actinomycetemcomitansmentioning
confidence: 99%
“…Prevention and treatment of pathologies in the superficial and deep marginal periodontium must be judiciously considered in the management of patients with hyperglycemia. It has been shown that keeping blood sugar levels under control has advantages over periodontal disease, while the treatment of periodontal disease improves metabolism in patients with diabetes [86]. Clear health strategies need to focus on periodontal disease, as a risk factor for diabetes and cardiovascular disease, through prevention and treatment programs for all chronic infections [87].…”
Section: T Forsythia a Actinomycetemcomitansmentioning
confidence: 99%
“…Several studies have shown the bidirectional relationship between periodontal disease and diabetes [1][2][3][4]. Both pathologies are highly prevalent worldwide, but the mechanisms linking them are not fully understood [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mohamed et al consider that chronic periodontitis is associated with disturbance of the local expressions of biomarkers related to the onset of type 2 diabetes and its medical complications in gingival crevicular fluid [2]. Casanova et al highlights that diabetes and periodontitis are chronic conditions that have a known reciprocal association, so that patients with diabetes have shown improvements in glycaemic control after receiving periodontal treatment, with HbA1c levels decreasing by about 0.4% [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To further highlight the importance of thoroughly inspecting the oral cavity, multiple studies have shown a positive correlation between periodontal disease and uncontrolled diabetes, cardiac conditions, stroke, and pregnancy. 8 Numerous systemic diseases can exhibit symptoms within the oral cavity, occasionally appearing before other clinical indications. Given the convenience of examination in this region, it becomes crucial for clinicians to recognize prevalent oral manifestations of diverse conditions, aiding in distinguishing between systemic issues and oral neoplastic changes.…”
Section: Introductionmentioning
confidence: 99%